Pemberdayaan Masyarakat dalam Pencegahan Pelecehan Seksual pada Anak di Aceh Barat: Model Edukasi dan Advokasi berbasis Kearifan Lokal - Hafinda, Tengku; Murlisa, Lia; Masni, Masni; Agustina, Maya; Putri, Nina Eka; Rahmi, Rina; Diana, Sari; Friwarti, Sri Dwi (LSM Catimore dan Sahabat, 2025)
Cases of child sexual abuse in West Aceh have been increasing at an alarming rate, necessitating a community-based prevention strategy. This study aims to empower the community in preventing sexual abuse through an education and advocacy model based on local wisdom. The research employs the Participatory Action Research (PAR) method, which involves the community in the process of problem identification, solution design, program implementation, evaluation, and monitoring. Activities include an initial survey, the development of educational materials, and training sessions for parents, teachers, and community leaders. The findings indicate an increase in community awareness of sexual abuse from 40% to 85%, as well as an improvement in understanding of reporting procedures from 30% to 80%. These results confirm that a community-based approach grounded in local wisdom is effective in raising public awareness of child protection, making it a sustainable prevention model.